2015
DOI: 10.1037/pspi0000034
|View full text |Cite
|
Sign up to set email alerts
|

Emotion regulation and depressive symptoms: Close relationships as social context and influence.

Abstract: Depression is associated with social dysfunction and maladaptive social environments, but mechanisms through which social relationships affect depressive psychopathology are unclear. We hypothesized that emotion regulation (ER) is such a mechanism, with outcomes of individuals’ ER efforts sensitive to the social context, and individuals’ ER strategy repertoire and use sensitive to social influence. In Study 1, a longitudinal study of community adults (N = 1,319), associations of individuals’ ER strategies with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
65
3
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 109 publications
(207 reference statements)
10
65
3
7
Order By: Relevance
“…Notably, effects of these emotional approach components depend in part on intrapersonal factors (e.g., gender; Juth, Dickerson, Zoccola, & Lam, 2015) and environmental contexts (e.g., social contexts receptive to emotional expression and processing; Stanton, Danoff-Burg et al, 2000), indicating that emotion regulation in coping with cancer does not occur in a vacuum. The notion that social factors may play a determining role is consistent with findings that individuals’ emotion regulation strategy use has different links with depressive symptoms depending on social connectedness versus loneliness (Marroquín & Nolen-Hoeksema, 2015). Understanding socially-relevant factors that moderate effects of emotional expression and processing among women with breast cancer may have important implications for treatment, as it may help identify women at higher risk for maladaptive coping outcomes, or suggest social targets in individually-focused treatment.…”
Section: Emotion Regulation Depression and Coping With Cancersupporting
confidence: 82%
See 3 more Smart Citations
“…Notably, effects of these emotional approach components depend in part on intrapersonal factors (e.g., gender; Juth, Dickerson, Zoccola, & Lam, 2015) and environmental contexts (e.g., social contexts receptive to emotional expression and processing; Stanton, Danoff-Burg et al, 2000), indicating that emotion regulation in coping with cancer does not occur in a vacuum. The notion that social factors may play a determining role is consistent with findings that individuals’ emotion regulation strategy use has different links with depressive symptoms depending on social connectedness versus loneliness (Marroquín & Nolen-Hoeksema, 2015). Understanding socially-relevant factors that moderate effects of emotional expression and processing among women with breast cancer may have important implications for treatment, as it may help identify women at higher risk for maladaptive coping outcomes, or suggest social targets in individually-focused treatment.…”
Section: Emotion Regulation Depression and Coping With Cancersupporting
confidence: 82%
“…Only among women higher in implicit loneliness, expressing less positive emotion and engaging in more causal processing during the essay task predicted higher depressive symptoms. The fact that these patterns were not apparent among less lonely women supports the hypothesis that intrapersonal emotion regulatory processes have stronger effects on depression and other mental health outcomes among more socially isolated individuals (Marroquín, 2011; Marroquín & Nolen-Hoeksema, 2015). The present findings are also consistent with evidence implicating dampened positive emotion (e.g., Bylsma et al, 2008) and elevated causal processing (e.g., rumination; Nolen-Hoeksema et al, 2008) in depression.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Thus, degree of emotional closeness may be an important social contextual factor for the experience of positive emotions in social settings, particularly for youth with social anxiety disorder. Some work has demonstrated that emotional closeness serves as a social form of regulation, helping to ease stress and physiological arousal (Marroquin & Nolen-Hoeksema, 2015). Therefore, presence of a close peer (either in one-on-one interactions or as a buffer for large peer group interactions) may help socially anxious youth to relax and enjoy positive experiences more so than the presence of less connected peers.…”
mentioning
confidence: 99%